(جعفرؔ بلوچ کی اُردو غزل(بہ حوالہ تصوُّرِ مرگ و حیات - Shamas, Dr. Saima (Zoraiz, 2022)
In this article, Jaffer Balochs’ concept of life and death in Urdu ghazal has been examined and salient features of this concept have been explored. His life and poetry represent high values of life. He is convinced of the purity of life and the majesty of death. His Urdu ghazal is composed of warmth, sincerity, and determination.